2015
DOI: 10.1039/c5cp03647j
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study of adsorption of imidazole, triazole, and tetrazole on oxidized copper surfaces: Cu2O(111) and Cu2O(111)-w/o-CuCUS

Abstract: Azoles and their derivatives are known for their corrosion inhibition ability for copper. For this reason the bonding of imidazole, triazole, and tetrazole-used as archetypal models of azole corrosion inhibitors-to Cu2O(111) and Cu2O(111)-w/o-Cu(CUS) was characterized using density functional theory (DFT) calculations. The former surface contains coordinatively-saturated (CSA) and coordinatively-unsaturated (CUS) Cu sites, whereas the latter lacks the CUS sites. We find that the molecules preferentially bond w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 50 publications
0
21
2
Order By: Relevance
“…The choice of the Cu 2 O(111) w/o +1Cu CUS model can be further justified by the fact that the relaxed stoichiometric Cu 2 O(111)r, though being a local minimum structure, is not thermodynamically stable [27]. However, in our previous study [17], we showed that molecular adsorption is able to compensate the thermodynamic deficiency of Cu CUS ions. Hence, it seems appropriate to maintain only those Cu CUS ions that bond with adsorbed molecules.…”
Section: Description Of Considered Surfacesmentioning
confidence: 99%
See 4 more Smart Citations
“…The choice of the Cu 2 O(111) w/o +1Cu CUS model can be further justified by the fact that the relaxed stoichiometric Cu 2 O(111)r, though being a local minimum structure, is not thermodynamically stable [27]. However, in our previous study [17], we showed that molecular adsorption is able to compensate the thermodynamic deficiency of Cu CUS ions. Hence, it seems appropriate to maintain only those Cu CUS ions that bond with adsorbed molecules.…”
Section: Description Of Considered Surfacesmentioning
confidence: 99%
“…By lower coverage, we do not mean an extra low coverage, but instead some intermediate coverage, which is low enough that it allows for focusing predominantly on the molecule-surface interactions, even though at such coverage the long-ranged dipole-dipole interactions [15,17,48] may not yet be insignificant. Intact molecules (MolH) typically adsorb with the molecular plane perpendicular to the surface (or nearly so) and form one N-Cu bond and one X-H· · · O hydrogen bond (X = C2 for ImiH or N1 for TriH and TetH), except when bonding to Cu Ovac sites (Figure 6), where ImiH binds with the N3 atom to two adjacent Cu Ovac ions and forms the C2-H· · · O sub hydrogen bond.…”
Section: Adsorption Of Standalone Molecules At Lower Coveragementioning
confidence: 99%
See 3 more Smart Citations